2018
DOI: 10.1016/j.ijvsm.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eimeria species among sheep and goats in Suez Governorate, Egypt

Abstract: HighlightsSubclinical infection with Eimeria spp. was detected in sheep (57.7%) and goats (60%).Infected sheep serum levels of protein and sodium showed a significant decrease.Extracted DNA from sporulated oocysts was successfully amplified at 100 bp band using PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
52
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 24 publications
13
52
0
4
Order By: Relevance
“…With regard to the sex, there is a significant difference between sex, in which the prevalence rate was higher in females (76.3%, n=371/486) as compared to males (68.3%, n= 302/442). This result agreed with that noted by El-Akabawy (1992) in Kaloubia who recorded that females were more susceptible to infection (82.3%) than males (78%), and Mohamaden et al, (2018) in Suez, Egypt who recorded that females showed a higher prevalence rate (69.1%) than males (48.4%). On the other hand, this result disagreed with Sulaiman et al, (2005) who observed that the highest infection rate was in males (58.3%) than females (37.11%), Idris et al (2012) who observed that male lambs (4.66%) were more susceptible to infection than females (4.15%), and Dabasa et al, (2017) who recorded males more infected (31%) than females (10.4%).…”
Section: With Regard Tosupporting
confidence: 92%
See 2 more Smart Citations
“…With regard to the sex, there is a significant difference between sex, in which the prevalence rate was higher in females (76.3%, n=371/486) as compared to males (68.3%, n= 302/442). This result agreed with that noted by El-Akabawy (1992) in Kaloubia who recorded that females were more susceptible to infection (82.3%) than males (78%), and Mohamaden et al, (2018) in Suez, Egypt who recorded that females showed a higher prevalence rate (69.1%) than males (48.4%). On the other hand, this result disagreed with Sulaiman et al, (2005) who observed that the highest infection rate was in males (58.3%) than females (37.11%), Idris et al (2012) who observed that male lambs (4.66%) were more susceptible to infection than females (4.15%), and Dabasa et al, (2017) who recorded males more infected (31%) than females (10.4%).…”
Section: With Regard Tosupporting
confidence: 92%
“…Double infection rate was in 29.7% (n=200/673) while mixed infection rate was in 43.7% (n=294/673). The present result nearly similar to that recorded by El-Akabawy (1992) in Kaloubia, who investigated that mixed infection with 2-9 different Eimeria species was 78.8%, Toulah (2007) in Saudi Arabia, who noticed that mixed infection with multiple infection with three species was 51.22%, Mohamaden et al, (2018) who detected that the mixed infection was 68.3% of the examined sheep in Suez, Egypt. On the other hand, it disagreed with that observed by El-Akabawy (1992) in Kaloubia, who investigated that single infection rate was 1.7% among examined sheep.…”
Section: With Regard Tosupporting
confidence: 91%
See 1 more Smart Citation
“…The host's immunity can change depending on the age and sex of the animal. In the earlier studies, findings of more prevalent Eimeria infections in females than males caused by some stress-factors such as pregnancy, lambing, and lactation were reported (6,27).…”
Section: Discussionmentioning
confidence: 97%
“…Studying the intensity of parasitic infection prevalence remains a need for animal's proper management and control measures. In Egypt, monitoring of helminthic and protozoal infections and their prevalence has been recorded among small ruminants (Soliman and Zalat 2003;El-Shahawy 2016;Sultan et al 2016;Elmadawy and Diab 2017;Mohamaden et al 2018). It is supposed that determination of the most prevailing GIP is imperative to shrink the economic losses in goat industry.…”
Section: Introductionmentioning
confidence: 99%